EFEK PENGHAMBATAN EKSTRAK MENGKUDU TERHADAP PERTUMBUHAN PATOGEN DAN PERKEMBANGAN PENYAKTT LAYU BAKTERI TANAMAN PISANG - ., Efri (Universitas Lampung, 2004)
Inhibitory effect of pace extraction on growth of pathogen and development of bacterial wilt of banana disease. Bacterial wilt of banana (Ralstonia solanacearum) is one of banana diseases that potentially destructs banana plants in some areas. A study on the effect of extract of pace plant against bacterial wilt of banana were carried out in laboratory and experimental farm of Plant Protection Department, College of Agriculture, University of Lampung from May until October 2003. The study consisted of in vitro and intact plant experiments. The treatments for both in vitro and intact plants were (1) steril water (control), (2) extract of pace fruit, (3) extract of pace fruit leaves, (4) extract of pace roots and (5) bactericide (agrymycin sulfate). In vitro study was conducted by using completely randomized design, while intact plant study was conducted by using completely randomized block design. The results showed that extract of fruit, leaf and root of pace suppressed the growth of R. solanacearum in vitro. Fruit extract had the highest ability in suppressing the growth of bacterial wilt. However, the application of all kind of extiact did not suppress the incident of bacterial wilt of banana plant.